PENGARUH HARGA DAN KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN (STUDI PADA PELANGGAN PT KERETA API INDONESIA DAOP IV SEMARANG) - Akhmad Fauzi Fachreza; Widayanto Widayanto (Universitas Diponegoro, 2020)
People nowadays increasingly require transportation services that can deliver to relatively distant places but take less time. One of the alternative is the train. Menoreh Train is an economy class train in DAOP IV Semarang which has been rejuvenated and is known as the Economy New Image. Menoreh Train is expected to provide comfort that will later increase customer satisfaction and loyalty. But there are still problems that customer loyalty has not been created. This type of research is explanatory research, using a questionnaire as a method of data collection. The research method used is the Non Probability Sampling technique with Purposive Sampling and Accidental Sampling methods. Samples collected by 100 respondents of Menoreh Train is selected based on consideration. The study uses a Partial Least Square analysis technique, which is estimated with the WarpPLS 6.0 program. The results of the analysis by WarpPLS explain that the test results of the direct influence on the research model are the effect of prices on customer loyalty shows positive and significant results, the effect of prices on satisfaction shows positive and significant results, the effect of service quality on satisfaction shows positive and significant results, the influence of service quality on customer loyalty shows positive and significant results, the effect of satisfaction on customer loyalty shows positive and significant results. Test the indirect effect of the research model that is the effect of prices on customer loyalty through satisfaction shows positive and significant results, the effect of service quality on customer loyalty through satisfaction shows positive and significant results. There is advice to PT. KAI DAOP IV Semarang based on the lowest recapitulation value given by respondents to the assessment indicators, namely increase ticket price competitiveness, add training programs, certifications, and more mature briefings to provide excellent service starting from the dispatch to the destination, continues to educate customers about quality product and services, optimize product and service quality, and evaluating performance in order to retain customers.